Analisis Geometrik Lokasi Rawan Laka di Jalan Lingkar Sumpiuh, Banyumas - Fakhri, Khoirudin; Wibowo, Agung Hari; Effendi, Achmad; Widyatmoko, Ari (Jurnal Proyek Teknik Sipil, 2024)
Safety road are closely related to geometric design, which includes road function, speed design, superelevation, and alignment. This paper is a geometric study to realize a safety road on Sumpiuh Ring Road, Banyumas Regency, Central Java. The locus of this research is the PI-2 and PI-3 bends located at STA. 22+213 to 22+348 which are two opposing bends that are close to each other. Measurement of existing shows that the transverse slope of the road cross-section at the peak of the PI-2 bend is 2.00% while at PI-3 it is 0.70%. With a speed of 60 km/hour, the driver will have difficulty controlling his vehicle due to centrifugal force. Such conditions make this location prone to accidents. From the analysis results, a transverse slope of 7.75% is required for PI-2, and 6.45% for PI-3. Construction adjustments need to be made to meet the needs of this superelevation design. The form of mitigation that can be done is by adding signs and road facilities such as guardrails, traffic signs such as chevron signs, speed reduction signs, rumble strips, and speed humps. This is intended to reduce the level of accidents at the location and reduce the fatalities.